Have reducing tonsillectomy rates in England led to increasing incidence of invasive Group A Streptococcus infections in children?. (16th April 2018) - Banigo, A.; Moinie, A.; Bleach, N.; Chand, M.; Chalker, V.; Lamagni, T.
Abstract : Objectives: To determine whether there is a correlation between falling tonsillectomy numbers and increasing numbers of tonsillitis admissions and invasive Group A β ‐haemolytic streptococcus (iGAS) infection in children aged 14 and under in England. Design: An observational cross‐sectional study was performed. Setting: The data extracted covered the period from 1991 until 2014. Participants: Hospital admissions for tonsillectomies, tonsillitis/pharyngitis and all diagnoses of iGAS in children aged 14 and under who had a tonsillectomy. Main outcome measures: Correlation between trends in tonsillectomies, tonsillitis/pharyngitis and iGAS. Results: Across all age groups, there was a dramatic reduction in the total number of tonsillectomies performed in England from 28 309 in 1990/1991, down to 6327 in 2013/2014 (77.7% reduction). The numbers of hospital admissions for management of acute tonsillitis and pharyngitis have risen dramatically. iGAS numbers have increased steadily over this time period and more than doubled in children aged 14 and under. There are significant negative correlations between the trend in iGAS infections and numbers of tonsillectomies in all ages. There are also strong positive correlations between the trend in numbers of tonsillitis episodes and the number of iGAS infections in all under 14‐year groups; the strongest correlation was seen in the 1‐ to 4‐year age group (+0.92 Pearson correlation coefficient). Conclusions: There appears to be a correlation between falling tonsillectomy numbers, increasing hospital admissions with tonsillitis and rising iGAS infection in England. Further studies are required to assess the aetiological role of tonsillitis in predisposing to iGAS infection and the potential societal benefit of tonsillectomies.